Microstructures and corrosion behaviors under sodium chloride aqueous conditions of Co-free non-equiatomic Al0.32CrFeTi0.73(Ni1.50-xMox) (x=0, 0.23) high entropy alloys - Xiaoyong Shu; Hao Wang; Jianping Zhao (Journal of Materials Research and Technology)
High entropy alloys (HEAs) were prepared using a vacuum arc melting method. The effect of Mo partially substituting Ni on the crystal structure and corrosion behaviors was studied. The results show that the HEAs exhibited a multiphase complex crystal structure which was composed of a BCC matrix and several intermetallic phases. The HEAs showed good corrosion resistance despite multiphase heterogeneity. But cyclic polarization showed that the HEAs were susceptible to pitting corrosion. Selective corrosion of Cr-depleted phases after polarization tests was attributed to the galvanic corrosion between Cr-depleted and Cr-rich phases. The spontaneous passive films on the HEAs surface were characterized by p-type semiconductor. Existence of Mo element of the HEAs accelerated passivation reaction kinetics, improved the stability of passive film, accordingly, acquired better general and pitting corrosion resistance.